2015
DOI: 10.1080/00218839.2016.1173427
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles of 20 species of monofloral bee pollen from China

Abstract: Fatty acids are important nutrients contained in bee pollen and vary greatly depending on the floral species. In this study, 20 species of monofloral bee pollen from China were collected to analyze fatty acid composition. Fatty acids were identified and quantified using gas chromatography-mass spectrometry with selected ion monitor (GC-MS/SIM) and compared with reference standards of 37 fatty acid methyl esters. Our results reveal that in virtually all bee pollen samples, a broad variety of fatty acids ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 34 publications
(33 reference statements)
1
24
0
9
Order By: Relevance
“…The high concentrations of stearic acid and arachidic acid measured in bee pollen collected during autumn and spring were related to the relative abundances of summer squash-harvested pollen in these seasons; summer squash has been reported as a rich source of these acids [20], and this factor may explain the strong positive correlation (r = 0.79) observed between stearic acid and arachidic acid. The stearic acid and arachidic acid concentrations in the tested samples were relatively similar to the corresponding concentrations measured in bee pollen collected from Saudi Arabia [20] and Serbia [27] but were higher than the corresponding concentrations measured in bee pollen from Poland, Korea [17], China [17,56], and Turkey [22].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The high concentrations of stearic acid and arachidic acid measured in bee pollen collected during autumn and spring were related to the relative abundances of summer squash-harvested pollen in these seasons; summer squash has been reported as a rich source of these acids [20], and this factor may explain the strong positive correlation (r = 0.79) observed between stearic acid and arachidic acid. The stearic acid and arachidic acid concentrations in the tested samples were relatively similar to the corresponding concentrations measured in bee pollen collected from Saudi Arabia [20] and Serbia [27] but were higher than the corresponding concentrations measured in bee pollen from Poland, Korea [17], China [17,56], and Turkey [22].…”
Section: Discussionsupporting
confidence: 63%
“…The high concentrations of oleic acid, palmitic acid, and linolenic acid in bee pollen harvested during spring, summer, and winter were related to the relative abundances of pollen collected from date palm, rapeseed, and sunflower plants during spring and winter and to the large amounts of alfalfa and sunflower pollen collected during summer. Alfalfa [20], date palm [20,55], rapeseed, and sunflower [20,27,56] have been reported to be rich in the previously listed FAs. Moreover, the lower concentration of oleic acid measured in bee pollen collected from summer squash [20] led to the lower oleic acid contents measured in the autumn-harvested bee pollen, which contained a large proportion of pollen collected from summer squash plants.…”
Section: Discussionmentioning
confidence: 99%
“…Bee pollen is a natural product with a rich composition mainly composed by proteins, vitamins, minerals, and carbohydrates, but also of amino acids, fatty acids, sterols, phospholipids, carotenoids and polyphenols [ 14 , 15 , 16 , 17 , 18 , 19 ]. Amores-Arrocha et al [ 20 , 21 ] stated bee pollen as a “Green nutrient activator”, as they observed improvements in fermentation kinetics (increased fermentation rate, reduction of the yeast lag phase and increased cell multiplication), both in white and red winemaking processes, although its use is currently not legally authorized for industrial processing.…”
Section: Introductionmentioning
confidence: 99%
“…There is variability in fatty acids of pollen samples stored by bees. Other authors evaluated the dehydrated pollen of M. mandacaia and commercial pollen of A. mellifera in an agro-industrial area and identified linoleic acid (C18:2D6) as the most abundant among the PUFAs (Dong et al, 2016;Santa-B arbara et al, 2015).…”
Section: Fatty Acid Profilementioning
confidence: 99%